2016
DOI: 10.1103/physreve.93.022902
|View full text |Cite
|
Sign up to set email alerts
|

Superdiffusive transport and energy localization in disordered granular crystals

Abstract: We study the spreading of initially localized excitations in one-dimensional disordered granular crystals. We thereby investigate localization phenomena in strongly nonlinear systems, which we demonstrate to differ fundamentally from localization in linear and weakly nonlinear systems. We conduct a thorough comparison of wave dynamics in chains with three different types of disorder-an uncorrelated (Anderson-like) disorder and two types of correlated disorders (which are produced by random dimer arrangements)-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 97 publications
(197 reference statements)
2
48
1
Order By: Relevance
“…In the on-site case, nonlinearity promotes localization (in the form of discrete breathers), rather than enabling mobility (in the form of traveling waves, as in FPU-type lattices). As a result, energy transport is only subdiffusive, whereas (as indicated above) superdiffusivity can occur for disordered granular crystals [6,127]. The study of disorder and nonlinear analogs of Anderson localization are important directions to pursue; they are accessible experimentally, and a systematic theoretical understanding of associated superdiffusive and subdiffusive transport should lead to important insights more generally on the interaction between disorder and nonlinearity.…”
Section: Traveling Structures In Configurations Other Than Monomer Chmentioning
confidence: 97%
See 1 more Smart Citation
“…In the on-site case, nonlinearity promotes localization (in the form of discrete breathers), rather than enabling mobility (in the form of traveling waves, as in FPU-type lattices). As a result, energy transport is only subdiffusive, whereas (as indicated above) superdiffusivity can occur for disordered granular crystals [6,127]. The study of disorder and nonlinear analogs of Anderson localization are important directions to pursue; they are accessible experimentally, and a systematic theoretical understanding of associated superdiffusive and subdiffusive transport should lead to important insights more generally on the interaction between disorder and nonlinearity.…”
Section: Traveling Structures In Configurations Other Than Monomer Chmentioning
confidence: 97%
“…In the broad context of condensed-matter physics, disorder (e.g., in the form of randomness) causes strong localization-so-called "Anderson localization"that affects the diffusivity of waves in disordered media [9,22]. Recent studies in the context of granular crystals have demonstrated computationally that such a phenomenon can be altered dramatically and can be even reversed (as superdiffusive transport can occur) by manipulating the nonlinearity strength in mechanical systems [6,127] (see also, e.g., [150,170]) and its potential "competition" with disorder. Such versatile dynamics associated with disorder and nonlinearity have only been studied very recently in granular crystals (and, more generally, they have not been studied much in lattice systems with inter-site interactions).…”
Section: Traveling Structures In Configurations Other Than Monomer Chmentioning
confidence: 99%
“…In this region, multiple scatterings occur because the presence of impurities has broken discrete translation symmetry, and successive interferences can then lead to complicated dynamics that depend on the distribution of impurities. A particular example of this phenomenon was investigated recently in the context of disordered granular chains [29].…”
Section: Multiple Impuritiesmentioning
confidence: 99%
“…Numerous studies have considered 'uniform' (i.e., monoatomic) one-dimensional (1D) lattices, which are chains in which each particle in the lattice is identical. However, particles need not be identical, and examinations of such 'heterogenous' lattices [51], with either periodic [43,44,65,79] or random [32,54] distributions of different particles, reveal a wealth of fascinating dynamics that do not arise in uniform lattices. Such dynamics include new families of solitary waves that have been observed in diatomic granular chains and which can exist only for discrete values of the ratio between the masses of the two particles in a diatomic unit [43].…”
mentioning
confidence: 99%